Conjunctival flap revisited: is it only a temporary solution for difficult corneal diseases? (Health Renaissance, 2012)
Background: The conjunctival flap technique, first described by Gundersen in 1958 has not undergone any major modifications since then, except for some variations depending upon pathology and surgeons’ preferences. Objective: To show the importance of conjunctival (Gundersen) flap in different corneal diseases where keratoplasty is not possible immediately. Methods: Out of total 113 non-healing corneal ulcers of different etiologies, nine patients had undergone total conjunctival flap and the rest of the patients had partial conjunctival flap. Out of 104 partial flaps, 31 patients had bipedicle flap and 73 patients had pedicle conjunctival flap. Diagnoses for Gundersen flap surgery included chronic Non-healing infective keratitis with and without impending perforation(93) (fungal -30, no organisms on culture-42 and bacterial- 21), Neurotrophic keratitis(4),Herpes simplex keratitis(9),Bullous keratopathy(2),Infected nonhealing graft(2),presumed infective perforated keratitis(3)(anterior chamber formed after pad and bandage). Results: Eight flaps retracted due to ulcer necrosis out of which seven cases got perforated with complete healing of ulcer. One case had to be eviscerated due to panophthalmitis. One hundred five cases got cured. Conclusion: Conjunctival flap is the urgent and most reliable remedy (temporary or even permanent in some pathologies) for chronic nonresolving infective and presumed infective keratitis with or without impending perforation, neurotrophic keratitis, chronic herpes simplex keratitis, bullous keratopathy and persistent nonhealing epithelial defects where there are no immediate facilities for corneal transplantation. Conjunctival flap should be familiarized and emphasized as a primary and complementary surgical solution where penetrating keratoplasty or lamellar keratoplasty can’t be immediately performed due to lack of corneal tissue. DOI: http://dx.doi.org/10.3126/hren.v10i1.6006 HREN 2012; 10(1): 40-45